Conservation Agriculture systems alter the electrical characteristics (Eh, pH and EC) of four soil types in France - Husson, O.; Brunet, A.; Babre, D.; Charpentier, H.; Durand, M.; Sarthou, Jean-Pierre (Elsevier, 2018)
The impacts of Conservation Agriculture (CA) practices on soil characteristics have been largely studied. However, changes in soil electrical properties induced by CA cropping systems have been rarely studied for soil electrical conductivity (EC), and have never been reported for soil redox potential (Eh). Electrical conductivity is a key parameter and is largely used in precision agriculture to characterize various soil properties. Conversely, soil redox potential (Eh) has been overlooked by agronomists despite its being able to provide essential information to characterize soil conditions. This study set out to characterize the changes in soil electrical properties (Eh, pH and EC) induced by CA practices. For four contrasting soil types, varying in texture, pH and organic matter content, we showed that CA alters soil electrical activity (characterized by Eh corrected to pH7 or pe + pH) and soil electrical conductivity. Fields under CA or conventional practices displayed reversed soil profiles for electrical activity: surface soil (0–5 cm) was found to be more oxidized under conventional systems than under CA practices, while the lower horizon (15–25 cm) was more oxidized in CA systems than in conventional systems. CA systems also decreased electrical conductivity when it was initially high, and increased it when it was low, especially in the surface horizon (0–5 cm). We discuss the possible mechanisms explaining such changes, the possible implications in the global functioning of soil/plant/microorganism system, and the interests and opportunities to use soil Eh-pH-EC as an indicator of soil health.